CHARACTERISTICS OF ANIMAL LANGUAGE: CASE OF A COCKATIEL TALKING IN PERSIAN - Ahmadreza Shoa Hasani, Hadi Shoa Hasani (International Journal of Research Science and Management, 2014)
This study was carried out to make insure of some aspects of language learning behavior of a Cockatiel parrot with the purpose revealing the characteristics of parrot’s language in contrast to human language. It is believed that some parrots could only mimic the speech sounds uttered by the human, and this behavior is not dealt with other characteristics of human language as Hockett declared in his studies. The findings of this qualitative research reveals that although animal language lacks the human language specifications, while could not be judged at the same criteria, but animals could communicate with humans in language. The sounds produced by Cockatiel in Persian, had meanings that were based on characteristics of human language.